2000
DOI: 10.1212/wnl.54.5.1050
|View full text |Cite
|
Sign up to set email alerts
|

Prospective validation of Consensus criteria for the diagnosis of dementia with Lewy bodies

Abstract: The Consensus criteria for DLB performed as well in this prospective study as those for AD and VaD, with a diagnostic sensitivity substantially higher than that reported by previous retrospective studies. DLB occurs in the absence of extrapyramidal features and in the presence of comorbid cerebrovascular disease. Fluctuation is an important diagnostic indicator, reliable measures of which need to be developed further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
229
3
9

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(249 citation statements)
references
References 37 publications
7
229
3
9
Order By: Relevance
“…3D-SSP images of patient 18 show typical reduction pattern of DLB. 3D-SSP images of patients 19 and 21 show severe reduction in frontal, parietal, and temporal lobes and mild-to-moderate reduction in precuneus and posterior cingulate gyrus, and primary sensorimotor cortex is spared so that this reduction pattern is considered as AD, but patient 19 shows unilateral mild occipital hypo- reported, in an autopsy study, relationships between primary and secondary clinical diagnoses that confirmed previous reports that the majority of DLB cases also met criteria for the other dementia subtypes, particularly possible AD (8). According to this report, the majority of probable DLB patients were diagnosed neuropathologically as DLB, but the majority of possible DLB patients were not diagnosed pathologically as DLB, but as progressive supranuclear palsy or AD.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…3D-SSP images of patient 18 show typical reduction pattern of DLB. 3D-SSP images of patients 19 and 21 show severe reduction in frontal, parietal, and temporal lobes and mild-to-moderate reduction in precuneus and posterior cingulate gyrus, and primary sensorimotor cortex is spared so that this reduction pattern is considered as AD, but patient 19 shows unilateral mild occipital hypo- reported, in an autopsy study, relationships between primary and secondary clinical diagnoses that confirmed previous reports that the majority of DLB cases also met criteria for the other dementia subtypes, particularly possible AD (8). According to this report, the majority of probable DLB patients were diagnosed neuropathologically as DLB, but the majority of possible DLB patients were not diagnosed pathologically as DLB, but as progressive supranuclear palsy or AD.…”
Section: Discussionsupporting
confidence: 80%
“…However, the differential diagnosis of DLB in contrast with other degenerative diseases such as Parkinson's disease (PD), AD, and vascular dementia may not be feasible because of those clinically overlapping symptoms, especially in the case of possible DLB. The reported sensitivity rates for a clinical diagnosis of probable DLB have varied from 0.22 to 0.83 and the specificity from 0.79 to 1.0 (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…We did not have autopsy confirmation of the diagnoses in the subjects, however we used a consensus clinical diagnosis, which we have previously shown to have good accuracy against autopsy [16]. In addition, all 9 of our DLB subjects who had dopamine transporter imaging had abnormal scans consistent with DLB as the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Nine of the DLB subjects had a 123 I-FP-CIT SPECT scan, all of whom demonstrated reduced dopamine transporter uptake in the basal ganglia. All diagnoses were made by consensus between two experienced clinicians, a method we have previously validated against autopsy diagnosis [16]. Diagnoses were made independent of MRI scanning.…”
Section: Subjectsmentioning
confidence: 99%
“…The majority were followed longitudinally at the Johns Hopkins University Morris Udall Parkinson's Disease Center, and the diagnosis of PD was confirmed at autopsy [6,17,20]. These individuals had histories of PD for 7-20 years, with or without dementia, and their brains had α-synuclein lesions in the SN and other brain regions [34]. There were no significant lesions indicative of other neurodegenerative disorders, i.e., tauopathies [13] or multiple system atrophy [18,40].…”
Section: Subjectsmentioning
confidence: 99%